Minimal thermal modeling of two-way thermomechanically coupled plates for nonlinear dynamics investigation. Issue 3 (3rd March 2020) - Saetta, Eduardo; Settimi, Valeria; Rega, Giuseppe
Abstract: Minimal thermal modeling of two-way thermomechanically coupled plates is addressed in the framework of a unified formulation of the underlying continuum problem. Variably refined reduced-order models are considered, and some main features of the relevant transient and steady responses to a variety of active thermal sources are investigated, by properly reconstructing 3D temperature configurations and energy balances. In comparison with a richer reduced model and available analytical solutions, a model with assumed cubic temperature distribution along the thickness has the advantage of being the minimal one still allowing to consider a wide set of boundary and body thermal excitations, while showing a comprehensive capability to reliably describe the thermal response. This appears of particular interest also in view of further pursuing a systematic, yet computationally demanding, investigation of the nonlinear dynamics of the coupled plate, in the cheapest possible way from both the mechanical and thermal viewpoint.